MOF-derived bimetallic sulfide electrode and preparation method and application thereof
Through the preparation method of MOF-derived bimetallic sulfide electrode, the problem of low controllability of the morphological structure design of metal sulfide electrode materials is solved by using hydrothermal method and vulcanization technology, and high specific capacitance and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411962247.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The morphological structure design of metal sulfide electrode materials is low, resulting in the need to improve the electrochemical performance.
The preparation method of MOF-derived bimetallic sulfide electrode is adopted, and the morphology structure of MOF is controlled by combining hydrothermal method and vulcanization, thereby regulating the morphology of the electrode and forming an electrode with a high specific capacitance.
The controllability and repeatability of the electrode morphology structure are achieved, and the specific capacitance and electrochemical performance of the electrode are improved. The area specific capacitance reaches 1131.8mF/cm2 under the current density of 1mA/cm2.
Smart Images

Figure CN119786280A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitors, and in particular to a MOF-derived bimetallic sulfide electrode and a preparation method and application thereof. Background Art
[0002] The research and development of green and environmentally friendly energy storage materials has also received more and more attention. Energy storage materials are functional materials that store energy through media or devices. They can be divided into physical energy storage, chemical energy storage and electromagnetic energy storage according to the energy storage method. Common energy storage materials include battery materials, hydrogen storage materials, supercapacitor materials and other environmentally friendly materials. Structural batteries, structural supercapacitors and structural dielectric capacitors are the most typical energy storage devices, but batteries have high energy density but low power density, while dielectric capacitors have high power density but low energy density. Supercapacitors are a new type of energy storage device between traditional capacitors and rechargeable batteries. Their energy storage capacity can reach hundreds or thousands of farads. Compared with traditional capacitors and batteries, supercapacitors have the characteristics of high power density, long cycle life, wide operating temperature range, maintenance-free and green environmental protection. They are widely used in the fields of automobiles, transportation, aviation and new energy.
[0003] The selection and preparation of electrode materials in supercapacitors play a vital role. Electrode materials are divided into double-layer electrode materials and pseudocapacitive electrode materials. Double-layer electrode materials are composed of carbon materials, and common ones include activated carbon, graphene, carbon nanotubes, carbon fibers, etc. Pseudocapacitive electrode materials include transition metal compounds and conductive polymers. Common transition metal compounds include metal oxides, metal sulfides, metal selenides, metal organic framework materials, etc., while conductive polymers include polyaniline, polypyrrole, etc. Electrodes constructed from pure carbon materials have low specific capacitance, which limits their application in supercapacitors.
[0004] In recent years, more and more researchers at home and abroad have combined metal compounds with carbon materials to improve the electrochemical performance of electrode materials. Among them, metal sulfides are widely used in the field of carbon materials due to their unique electronic structure and abundant redox reaction active sites. At present, bimetallic sulfides are mostly prepared by one-step hydrothermal method, and the morphology and structure design of electrode materials prepared by one-step hydrothermal method has low controllability.
[0005] Publication No. CN110745870A discloses a bimetallic sulfide electrode material. The preparation method of the electrode material is: dissolving zinc acetate dihydrate and cobalt acetate tetrahydrate in deionized water, stirring and mixing to obtain a pink mixed solution; then introducing thiourea into the pink mixed solution, continuing to stir, to obtain a dark purple solution; finally, adding the purple solution into a reactor to perform a hydrothermal reaction; after the reaction is completed, naturally cooling to room temperature, centrifugally washing with distilled water and ethanol and drying, Zn 0.76 Co 0.24S electrode material.
[0006] CN118248467A discloses an electrode material and a preparation method thereof and a capacitor, which relates to the field of new energy technology. The electrode material includes iron and cobalt bimetallic and nitrogen and sulfur doped carbon materials, which are arranged in a porous nano-spherical structure. Binary metal sulfides formed by iron, cobalt and sulfur contact each other to form an interface region to induce a synergistic effect, reduce the reaction activation energy of the electrode-electrolyte, reduce the thermodynamic polarization and kinetic polarization related to electrons, promote the diffusion and transport of electrons and ions, and improve the specific capacity, rate characteristics and central compound conductivity of the electrode material; the introduction of nitrogen-doped carbon enhances the conductivity of the electrode material, improves the cycle stability of the electrode material in the electrolyte, and prolongs the cycle life of the electrode material.
[0007] However, the morphological structure design of the electrode materials prepared by this method has low controllability, and most of them can only form the shape of needle-like clusters, while the surface structure has a great influence on its electrochemical performance. Summary of the invention
[0008] In view of the problems that the morphology of metal sulfide electrode materials has low controllability and the electrochemical performance needs to be improved, the present invention provides a method for preparing a MOF-derived bimetallic sulfide electrode. The electrode morphology can be controlled by controlling the morphology of MOF to obtain an electrode with high specific capacitance.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A method for preparing a MOF-derived bimetallic sulfide electrode comprises the steps of:
[0011] Step 1, mixing precursor solutions of two metal salts and a ligand solution to obtain a bimetallic MOF precursor solution;
[0012] Step 2, activating, cleaning and drying the surface of the conductive substrate;
[0013] Step 3, placing the activated conductive substrate in the bimetallic MOF precursor solution of step 1, washing and drying after hydrothermal reaction to obtain a bimetallic MOF-coated conductive substrate;
[0014] Step 4, spreading sulfur powder on the surface of the conductive substrate in step 3, subjecting the substrate to a sulfurization treatment in an inert environment, and obtaining the bimetallic sulfide electrode after washing and drying.
[0015] The present invention adopts a combination of hydrothermal method and sulfurization, firstly prepares the MOF structure by hydrothermal method, regulates its surface structure, and further obtains the bimetallic sulfide electrode by sulfurization etching. This process does not change the microscopic morphology of MOF, and its morphology is controllable and reproducible, and is no longer limited to a single needle-like cluster structure. In addition, the prepared bimetallic sulfide electrode has abundant metal sulfide sites, and the electrode has a high specific capacitance and exhibits good electrochemical performance. At 1 mA / cm 2 The area specific capacitance can reach up to 1131.8mF / cm at the current density 2 .
[0016] The metal salt is a soluble salt of any two metals of nickel, cobalt, copper, iron, titanium, tin, zinc, aluminum, manganese, and molybdenum; the metal salt includes any one or more of nitrates, sulfates, chlorides, and phosphates.
[0017] The ligand includes any one of imidazole, thiourea, quinoline, and phthalic acid;
[0018] Preferably, the bimetallic salt solution is nickel nitrate hexahydrate solution, cobalt nitrate hexahydrate solution, copper nitrate trihydrate solution, and manganese nitrate tetrahydrate solution. Nitrates are relatively stable at room temperature, easily hydrolyzed, and react rapidly. The generated nanostructure has a high surface area and can provide more contact area.
[0019] Preferably, the ligand is terephthalic acid or imidazole.
[0020] The solvents used in the metal salt precursor solution and the ligand solution include any one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, an acid solution, and an alkaline solution.
[0021] The conductive substrate includes any one of fiber woven fabric, carbon cloth, nickel foam, copper foam, and ITO conductive glass; the activation method includes any one of acid activation, alkali activation, and high temperature activation. Preferably, the conductive substrate is a carbon fiber woven fabric during use. Before use, the carbon fiber woven fabric is de-sizing, cleaned, and dried to obtain a carbon fiber woven conductive substrate; the carbon fiber woven fabric, as a self-supporting substrate, not only provides a wide growth space for the bimetallic sulfide active material, but also enables the prepared electrode material to have excellent mechanical properties and conductivity, and can give full play to the capacitive characteristics of transition metal sulfides.
[0022] Further preferably, the carbon fiber fabric is T300; T300 has high electrical conductivity and excellent mechanical properties of tensile strength and tensile modulus, can act as a current collector during charging and discharging, provide a faster electron transfer rate, and can provide a high-strength loading substrate for the bimetallic sulfide active material.
[0023] Preferably, the activation process of the carbon fiber fabric includes nitric acid soaking and desizing, such as soaking for 12 to 36 hours at a concentration of concentrated nitric acid to deionized water of 1:2 to 2:1; preferably, soaking for 12 hours at a ratio of nitric acid to deionized water of 2:1.
[0024] The molar concentration of the precursor solution of the metal salt is 0.01-0.6M for the ligand solution; the molar ratio of the two metals in the precursor solution of the two metal salts is (0.5-3):(3-0.5); the total molar ratio of the ligand and the metal salt is (0.5-5):(0.5-2).
[0025] Preferably, the concentration of the bimetallic salt solution is 0.15M, the concentration of the ligand solution is 0.15M, the molar ratio of the metals in the bimetallic solution is 1:2 to 2:1, and the ratio of the ligand to the metal salt is 1:1; the amount of the ligand is changed from the original amount to 2 times. If the two metals are not mixed and stirred in a certain molar ratio, it is not conducive to forming a complete and uniform MOF morphology; if the concentration is too high, the MOF precursor solution may have formed particles and precipitated, and cannot adhere to the surface of the conductive substrate.
[0026] In step 3, the hydrothermal reaction temperature is 60-200°C, and the reaction time is 1-24h. Preferably, the hydrothermal temperature of the reactor is 100-160°C, and the treatment time is 8-12h. If the reaction temperature is too high, the surface deposition layer is too thick, and it is difficult to obtain the best morphology; if the treatment temperature is too low, the MOF morphology cannot grow on the carbon fiber surface. If the treatment time is too short, the MOF growth amount is too small, and the carbon fiber cannot be evenly coated, resulting in an uneven surface; if the treatment time is too long, the morphology is not uniform, which easily leads to surface layer accumulation and agglomeration, and good electrochemical performance cannot be obtained.
[0027] In step 4, the mass ratio of sulfur powder to the bimetallic MOF on the conductive substrate is greater than 1:1. Preferably, the total mass ratio of sulfur powder to the bimetallic MOF on the surface of the carbon cloth is 1:1 to 1.5:1. If the sulfur powder is insufficient, the sulfurization reaction is incomplete. If the sulfur powder is excessive, it will cause waste and inconvenience in cleaning the residual sulfur powder.
[0028] In step 4, the vulcanization temperature is 200-500° C., and the vulcanization time is 60-240 min.
[0029] Preferably, the cleaning in steps 2 and 3 is cleaning with water and anhydrous ethanol to wash away impurities that have not reacted or remain on the surface; the purpose of cleaning with carbon disulfide in step 4 is to remove unreacted sulfur on the electrode surface.
[0030] The above drying conditions are drying at 50-70°C for 6-24 hours, such as drying at 60°C for 1 hour.
[0031] The present invention also provides a MOF-derived bimetallic sulfide electrode prepared according to the preparation method. The electrode has a bimetallic sulfide tightly combined with a substrate and has excellent electrochemical properties. 2 The area specific capacitance of the electrode reaches 1131.8mF / cm at a current density of 2 , can be applied in the field of supercapacitors.
[0032] The present invention also provides a supercapacitor, comprising the MOF-derived bimetallic sulfide electrode, an activated carbon electrode, and a polyvinyl alcohol / potassium hydroxide electrolyte.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) Compared with the commonly used one-step hydrothermal method for preparing bimetallic sulfides, the synthesis method of the present invention for preparing MOF-derived bimetallic sulfide electrodes can regulate the morphology of metal sulfides by controlling the surface structure of the precursor; compared with the multi-step hydrothermal method for preparing bimetallic sulfides, the preparation time is shortened, the cost is reduced, and the waste liquid generation is reduced. The electrode material obtained has excellent mechanical properties and conductivity, and can give full play to the capacitive characteristics of transition metal sulfides under the support of a conductive substrate.
[0035] (2) In the present invention, the morphology and structure of the metal precursor can be regulated by adjusting the composition of the metal salt, thereby further achieving the regulation of the morphology and composition of the bimetallic sulfide, and the optimization of the structure and composition can be achieved in a simple way, so that the electrode material has better electrochemical performance at 1 mA / cm 2 The area specific capacitance of the electrode reaches 1131.8mF / cm at a current density of 2 , assembled into a flexible asymmetric supercapacitor, at 3.2 mW / cm 2 At a power density of 0.172mWh / cm 2 The energy density can be applied to the field of supercapacitor energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 These are SEM images of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 1 before and after sulfurization.
[0037] Figure 2 This is the voltammetric curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 1.
[0038] Figure 3 This is the constant current charge and discharge curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 1.
[0039] Figure 4 These are SEM images of the MOF-derived bimetallic sulfide electrode material (NiCu-S@ACFF) prepared in Example 2 before and after sulfurization.
[0040] Figure 5 This is the voltammetric curve of the MOF-derived bimetallic sulfide electrode material (NiCu-S@ACFF) prepared in Example 2.
[0041] Figure 6 This is the constant current charge and discharge curve of the MOF-derived bimetallic sulfide electrode material (NiCu-S@ACFF) prepared in Example 2.
[0042] Figure 7 These are SEM images of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in Example 3 before and after sulfurization.
[0043] Figure 8 This is the voltammetric curve of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in Example 3.
[0044] Fig. 9 This is the constant current charge and discharge curve of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in Example 3.
[0045] Fig.10 This is the SEM image of the pure carbon fiber fabric (CFF) of Comparative Example 1.
[0046] Fig.11 This is the voltammetric curve of pure carbon fiber fabric (CFF) in comparative example 1.
[0047] Fig.12 This is the constant current charge and discharge curve of pure carbon fiber fabric (CFF) in comparative example 1.
[0048] Fig.13 This is the voltammetric curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 4.
[0049] Fig.14 This is the constant current charge and discharge curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 4.
[0050] Fig.15 This is the voltammetric curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 5.
[0051] Fig.16This is the constant current charge and discharge curve of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in Example 5.
[0052] Fig.17 The volt-ampere curve of the flexible asymmetric supercapacitor device (NiCo-S@ACFF / / AC) prepared for the application example.
[0053] Fig.18 This is the constant current charge and discharge curve of the flexible asymmetric supercapacitor device (NiCo-S@ACFF / / AC) prepared in the application example.
[0054] Fig.19 Ragone plot of the flexible asymmetric supercapacitor device (NiCo-S@ACFF / / AC) prepared for the application example. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0056] The raw materials used in the following specific embodiments are all purchased from the market.
[0057] Example 1
[0058] Step 1: Use a measuring cylinder to weigh 80 ml of 68% concentrated nitric acid, add it to a beaker containing 40 ml of deionized water, and stir it evenly with a glass rod to obtain a concentrated nitric acid solution. Cut a 2 cm × 2 cm piece of carbon fiber fabric (CFF), soak it in the concentrated nitric acid solution for 12 hours, then wash it with anhydrous ethanol and deionized water several times, and dry it in a forced air drying oven at 60 ° C for 12 hours to obtain an activated carbon fiber fabric (ACFF).
[0059] Step 2, add 6mmol of terephthalic acid to 25ml of N,N-dimethylformamide and stir for 30min to obtain solution A. Add 6mmol of Ni(NO3)2·6H2O and Co(NO3)2·6H2O to 25ml of deionized water (Ni and Co feed ratio is 1:2), stir for 30min to obtain solution B. Mix solution A and solution B and stir magnetically for 10min. Then transfer the above precursor solution to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, add the pretreated carbon fiber cloth, tighten the reactor and put it into the oven, and react at 120℃ for 12h. After the reactor is naturally cooled to room temperature, take out the carbon cloth grown with MOF precursor, wash it with anhydrous ethanol and deionized water several times, and then put it into the oven at 60℃ to dry for 12h to obtain NiCo-MOF@ACFF.
[0060] Step 3, sulfurize NiCo-MOF@ACFF: Place the sample in a quartz boat, sprinkle sulfur powder on the surface, place it in a tube furnace, heat it from room temperature to 350°C at a heating rate of 5°C / min under N2 atmosphere, and react at 350°C for 2h. After the tube furnace is cooled to room temperature, take out the annealed sample, wash it repeatedly with carbon disulfide and anhydrous ethanol, and then place it in an oven at 60°C for 12h to obtain NiCo-S@ACFF.
[0061] Figure 1 (a) is the SEM of NiCo-MOF@ACFF prepared in step 2. Figure 1 (b) is a scanning electron microscope image of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in this embodiment. It can be seen from the figure that NiCo-MOF is stacked on the surface of carbon fiber in a nanosheet structure. After sulfurization, the nanostructure has not changed, and NiCo-S is still in a nanosheet structure, evenly distributed on the surface of carbon fiber, and built into a petal structure with a high specific surface area, and there is no agglomeration and exposed carbon fiber, and sulfide active sites appear on the surface. This high specific surface area and rich active sites can improve the transfer and exchange of ions in the electrolyte, which is beneficial to improve the capacitance performance of the electrode material. The morphology of the electrode material in this example has almost no change before and after sulfurization, which shows that the morphology of the sulfurized electrode can be controlled by designing the morphology of MOF.
[0062] Figure 2The cyclic voltammetry curve (CV) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in this example at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, and a redox peak with pseudocapacitive characteristics is also generated, indicating that the electrode material undergoes a Faraday redox reaction in the electrochemical test, and gradually changes with the change of the scan rate. When the scan rate is higher, the oxidation peak gradually shifts to the right, the reduction peak shifts to the left, and the peak intensity gradually weakens. This is because at a high scan rate, the electrolyte does not have time to enter the electrode material to participate in the redox reaction, making the intensity weaker.
[0063] Figure 3 The constant current charge-discharge curve (GCD) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared in this example at different current densities with 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 ) presents a triangular GCD curve with obvious redox reaction behavior, which is consistent with the CV curve test results. The longer the GCD discharge time, the better the capacitance performance. 2 The current density is 1131.8mF / cm 2 The area specific capacitance decreases with the increase of current density. 2 The high current density of 322.5·mF / cm 2 This is because the electrolyte does not have time to enter the interior of the electrode material under high current density, and the bimetallic sulfide (NiCo-S) electrode material cannot completely undergo redox reaction.
[0064] Example 2
[0065] The preparation method of the MOF-derived bimetallic sulfide electrode material in Example 2 is the same as that in Example 1, except that cobalt nitrate is replaced with copper nitrate, and the prepared bimetallic sulfide electrode material is NiCu-S@ACFF.
[0066] Figure 4 (a) is the SEM of the MOF structure NiCu-MOF@ACFF before sulfurization. Figure 4(b) is a scanning electron microscope image of the MOF-derived bimetallic sulfide electrode material (NiCu-MOF@ACFF) prepared in this example. NiCu-S after etching with sulfur powder on NiCu-MOF is in a micron sheet structure, evenly distributed on the surface of carbon fiber, overlapping each other to form an interconnected network structure, which can provide a channel for the electrolyte, accelerate the transfer and storage of electrons and ions, and help improve the capacitance performance of the electrode material. This example can also illustrate that the morphology of the sulfide electrode can be controlled by designing the morphology of MOF.
[0067] Figure 5 The cyclic voltammetry curve (CV) of the MOF-derived bimetallic sulfide electrode material (NiCu-S@ACFF) prepared in this example at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, and a redox peak with pseudocapacitive characteristics is also generated, indicating that the electrode material undergoes a Faraday redox reaction in the electrochemical test, and gradually changes with the change of the scan rate. When the scan rate is higher, the oxidation peak shifts to the right, the reduction peak shifts to the left, and the peak intensity gradually weakens. This is because at a high scan rate, the electrolyte does not have time to enter the electrode material to participate in the redox reaction, causing the intensity to weaken.
[0068] Figure 6 The constant current charge-discharge curve (GCD) of the MOF-derived bimetallic sulfide electrode material (NiCu-S@ACFF) prepared in this example at different current densities with 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 ) presents a triangular GCD curve with obvious redox reaction behavior, which is consistent with the CV curve test results. The longer the GCD discharge time, the better the capacitance performance. 2 The current density is 992.3mF / cm 2 The area specific capacitance decreases with the increase of current density. 2 The high current density of 97.5 mF / cm 2 This is because the electrolyte does not have time to enter the interior of the electrode material under high current density, and the bimetallic sulfide (NiCu-S) electrode material cannot completely undergo redox reaction.
[0069] Example 3
[0070] The preparation method of the MOF-derived bimetallic sulfide electrode material in Example 3 is the same as that in Example 1, except that cobalt nitrate is replaced with manganese nitrate, and the prepared bimetallic sulfide electrode material is NiMn-S@ACFF.
[0071] Figure 7 (a) is the SEM of the prepared MOF structure NiMn-MOF@ACFF before sulfurization. Figure 7 (b) is a scanning electron microscope image of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in this embodiment. NiMn-MOF@ACFF has a block structure, evenly distributed on the surface of carbon fiber, stacked on each other, and after sulfur powder etching and sulfurization, the structure of NiMn-S is not changed, and metal sulfide active sites are etched on the surface. However, the surface area of this structure is relatively general, there is no interconnected network structure and high specific surface area, and the electrode material cannot completely react with the electrolyte. This example also further illustrates that the morphology of the sulfurized electrode can be controlled by designing the morphology of MOF.
[0072] Figure 8 The cyclic voltammetry curve (CV) of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in this example at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, and a redox peak with pseudocapacitive characteristics is also generated, indicating that the electrode material undergoes a Faraday redox reaction in the electrochemical test, and gradually changes with the change of the scan rate. When the scan rate is higher, the oxidation peak shifts to the right, the reduction peak shifts to the left, and the peak intensity gradually weakens. This is because at a high scan rate, the electrolyte does not have time to enter the electrode material to participate in the redox reaction. Compared with Example 1 and Example 2, the curve area of CV is significantly smaller.
[0073] Fig. 9 The constant current charge-discharge curve (GCD) of the MOF-derived bimetallic sulfide electrode material (NiMn-S@ACFF) prepared in this example at different current densities with 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 ) presents a triangular GCD curve with redox behavior, which is consistent with the CV curve test results. The longer the GCD discharge time, the better the capacitance performance. 2 The current density is 182.4mF / cm 2 The area specific capacitance decreases with the increase of current density. 2The high current density of 28.2 mF / cm 2 This is because the electrolyte does not have time to enter the interior of the electrode material under high current density, and the bimetallic sulfide (NiMn-S) electrode material cannot completely undergo redox reaction.
[0074] Comparative Example
[0075] The comparative example is pure T300 carbon fiber fabric (CFF), cut into 2×2cm 2 Carbon fiber fabric.
[0076] Fig.10 The scanning electron microscope image of the CFF electrode material prepared in this comparative example shows that the carbon fiber has shallow longitudinal grooves, a smooth surface with few impurity particles, and a low specific surface area of only 0.7 m 2 / g.
[0077] Fig.11 The cyclic voltammetry curve (CV) of the CFF electrode material prepared for this comparative example at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, the curve presents a double electric layer type, and the curve area is small, indicating that the specific capacitance of CFF is low.
[0078] Fig.12 The constant current charge-discharge curve (GCD) of the CFF electrode material prepared in this comparative example at different current densities with 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 The GCD curve of the electrode material is an isosceles triangle, with an obvious double-layer type, which is consistent with the CV curve test results. 2 The current density is 23.1mF / cm 2 The area specific capacitance of the carbon cloth is shown as poor. Compared with Examples 1-3, after bimetallic sulfide is deposited on the surface of the carbon cloth, the area specific capacitance is further improved.
[0079] Example 4
[0080] The preparation method of the MOF-derived bimetallic sulfide electrode material in Example 4 is the same as that in Example 1, except that the feed ratio of nickel nitrate to cobalt nitrate is adjusted to 1:1 to prepare the bimetallic sulfide electrode material (NiCo-S@ACFF).
[0081] Fig.13The cyclic voltammetry curve (CV) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared with a nickel-cobalt feed ratio of 1:1 in this embodiment at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, and a redox peak with pseudocapacitance characteristics is also generated, indicating that the energy storage behavior of the metal sulfide electrode material is mainly pseudocapacitance, and gradually changes with the change of the scan rate. When the scan rate is higher, the oxidation peak gradually shifts to the right, the reduction peak shifts to the left, and the peak intensity gradually weakens. This is because at a high scan rate, the electrolyte does not have time to enter the electrode material to participate in a complete redox reaction.
[0082] Fig.14 The constant current charge-discharge curve (GCD) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared with a nickel-cobalt feed ratio of 1:1 at different current densities and 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 The GCD curve of the electrode material is triangular and has a platform with pseudocapacitive characteristics, which is consistent with the CV curve test results. The longer the GCD discharge time, the better the capacitance performance. 2 The current density is 881.8mF / cm 2 The area specific capacitance decreases with the increase of current density. 2 The high current density of 320.8·mF / cm 2 This is because the bimetallic sulfide (NiCo-S) electrode material cannot completely undergo redox reactions at high current densities.
[0083] Example 5
[0084] The preparation method of the MOF-derived bimetallic sulfide electrode material in Example 5 is the same as that in Example 1, except that the feed ratio of nickel nitrate to cobalt nitrate is adjusted to 2:1 to prepare the bimetallic sulfide electrode material (NiCo-S@ACFF).
[0085] Fig.15The cyclic voltammetry curve (CV) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared with a nickel-cobalt feed ratio of 2:1 in this embodiment at different scan rates with 3M KOH as the electrolyte. The figure shows that the area of the CV curve gradually increases with the increase of the scan rate, and a redox peak with pseudocapacitive characteristics is also generated, indicating that the electrode material undergoes a Faraday redox reaction in the electrochemical test, and gradually changes with the change of the scan rate. When the scan rate is higher, the oxidation peak gradually shifts to the right, the reduction peak shifts to the left, and the peak intensity gradually weakens. This is because at a high scan rate, the electrolyte does not have time to enter the electrode material to participate in the redox reaction, making the intensity weaker.
[0086] Fig.16 The constant current charge-discharge curve (GCD) of the MOF-derived bimetallic sulfide electrode material (NiCo-S@ACFF) prepared with a nickel-cobalt feed ratio of 2:1 at different current densities and 3M KOH as the electrolyte. The figure shows that at different current densities (1 / 2 / 3 / 5 / 10mA / cm 2 The GCD curve of the electrode material is triangular and has a platform with pseudocapacitive characteristics, which is consistent with the CV curve test results. The longer the GCD discharge time, the better the capacitance performance. 2 The current density is 665.5mF / cm 2 The area specific capacitance decreases with the increase of current density. 2 The high current density of 177.5·mF / cm 2 The area specific capacitance.
[0087] Application Examples
[0088] The flexible asymmetric supercapacitor in the application example is prepared by using NiCo-S@ACFF as the positive electrode, AC@CFF as the negative electrode, and PVA-KOH gel as the electrolyte to assemble a flexible all-solid-state asymmetric supercapacitor (1cm×2cm). The specific steps are as follows: put the positive and negative electrodes into the PVA-KOH gel and soak them completely, then take them out, and after the gel is naturally cooled and solidified at room temperature, overlap the positive and negative electrodes to form a flexible asymmetric supercapacitor (FASC).
[0089] Fig.17The FASC prepared for this application example uses two electrodes for testing, and the cyclic voltammetry (CV) curves at different scan rates are shown. The figure shows that the operating voltage window of the FASC device is 0-1.6V, and it has good capacitive performance. As can be seen from the figure, with the increase of the scan rate, the area of the CV curve gradually increases, and the shape does not undergo obvious deformation, indicating that the FASC device has good stability. It was further observed that the CV curve produced a clear redox peak, indicating that the device underwent a Faraday reaction during the reaction, which is a typical supercapacitor pseudocapacitive behavior.
[0090] Fig.18 The FASC prepared for this application example was tested using two electrodes. The FASC device was tested at 4-20 mA / cm2 in a voltage window of 0-1.6 V. 2 Constant current charge and discharge curves (GCD) at different current densities. It can be seen from the figure that GCD has a unique charge and discharge platform, which can verify the battery behavior of FASC devices, which is consistent with the CV results. FASC devices have a constant current charge and discharge curve at 4, 6, 8, 10, 15 and 20 mA / cm 2 The area specific capacitances at current densities of 483.3, 319.5, 314.1, 301.9, 263.5 and 218.8 mF / cm 2 It can be seen that when the current density increases to 20mA / cm 2 When , the FASC device has a rate performance of 45.3%.
[0091] Fig.19 The Ragone diagram of the energy density and power density of the FASC prepared for this application example is shown in the figure. The performance of different energy storage devices and the FASC device prepared in this experiment are compared. 2 At a power density of 0.172mWh / cm 2 The energy density of the device is 16.004mW / cm 2 At a power density of 0.078mWh / cm 2 The energy density of FASC devices shows that the FASC devices have excellent electrochemical performance. In addition, compared with other flexible supercapacitor devices prepared by carbon cloth-based composite electrodes, the FASC devices prepared in this experiment also have certain advantages in energy density and power density. It can be seen that the NiCo-S@ACFF / / AC device has relatively excellent energy storage performance.
Claims
1. A method for preparing a MOF-derived bimetallic sulfide electrode, characterized in that: Includes steps: Step 1, mixing precursor solutions of two metal salts and a ligand solution to obtain a bimetallic MOF precursor solution; Step 2, activating, cleaning and drying the surface of the conductive substrate; Step 3, placing the activated conductive substrate in the bimetallic MOF precursor solution of step 1, washing and drying after hydrothermal reaction to obtain a bimetallic MOF-coated conductive substrate; Step 4, spreading sulfur powder on the surface of the conductive substrate in step 3, subjecting the substrate to a sulfurization treatment in an inert environment, and obtaining the bimetallic sulfide electrode after washing and drying.
2. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: The metal salt is a soluble salt of any two metals selected from nickel, cobalt, copper, iron, titanium, tin, zinc, aluminum, manganese and molybdenum; The metal salt includes any one or more of nitrate, sulfate, chloride and phosphate.
3. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: The ligand includes any one of imidazole, thiourea, quinoline, and phthalic acid; The solvents used in the metal salt precursor solution and the ligand solution include any one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, an acid solution, and an alkaline solution.
4. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: The conductive substrate includes any one of fiber woven cloth, carbon cloth, foamed nickel, foamed copper, and ITO conductive glass; the activation method includes any one of acid activation, alkali activation, and high-temperature activation.
5. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: The molar concentration of the precursor solution of the metal salt is 0.01-0.6M for the ligand solution; the molar ratio of the two metals in the precursor solution of the two metal salts is (0.5-3):(3-0.5); the total molar ratio of the ligand and the metal salt is (0.5-5):(0.5-2).
6. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: In step 3, the hydrothermal reaction temperature is 60 to 200° C., and the reaction time is 1 to 24 hours.
7. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: In step 4, the mass ratio of sulfur powder to the bimetallic MOF on the conductive substrate is greater than 1:
1.
8. The method for preparing a MOF-derived bimetallic sulfide electrode according to claim 1, characterized in that: In step 4, the vulcanization temperature is 200-500° C., and the vulcanization time is 60-240 min.
9. A MOF-derived bimetallic sulfide electrode prepared according to the preparation method according to any one of claims 1 to 8.
10. A supercapacitor, characterized in that: Comprising the bimetallic sulfide electrode as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of bimetal sulfide supercapacitor electrode material
CN110745870A
Preparation method of bismuth-doped bimetallic sulfide electrode for electro-catalytic oxidation of urea
CN112080759A
Preparation method of self-supporting electrode with in-situ growth of bimetallic chalcogenide catalyst on surface
CN118326426A
Method for preparing ni-containing cus / c composite material, and use thereof
WO2022016763A1